A meeting of positive behaviors: The relations of three aspects of flexibility with character strengths - Vylobkova, Valentina; Heintz, Sonja (Frontiers in Psychology, 2023)
The adaptation of own plans and behaviors to new circumstances seems to be a desirable personal quality in the modern world. However, Lavy (2020) argues that adaptability cannot be transferred to a single character strength. The present research examines this assumption using typical and daily behaviors of three aspects of flexibility (predictability, adaptability and orderliness) and 24 character strengths. Across two studies (N1=283, N2=188), flexibility showed a consistent and large overlap with character strengths. Adaptability was positively related to most of the strengths. Predictability was positively related to humility and prudence, and orderliness to perseverance, prudence, and self-regulation. These results support Lavy`s assumption and build a strong basis for further examining the relationships and interplay between flexibility and character strengths. They also constitute an important first step toward integrative positive interventions that target relevant aspects of flexibility and character.